Native speaker - Lee, Chang-rae (Riverhead Books, 1996)
Korean-American Henry Park is a "surreptitious, B+ student of life, illegal alien, emotional alien, yellow peril: neo-American, stranger, follower, traitor, spy ..." or so says his wife, in the list she writes upon leaving him. Henry is forever uncertain of his place, a perpetual outsider looking at American culture from a distance. As a man of two worlds, he is beginning to fear that he has betrayed both -- and belongs to neither.